If there were no Japan a cultural memoir - Pulvers, Roger 1944- (Japan library (Shuppan Bunka Sangy?o Shink?o Zaidan), 2015)
"Originally published in Japanese, If There Were No Japan: A Cultural Memoir was acclaimed for its insights into Japanese life, bringing together aspects of history, culture and everyday life to paint an original and revealing portrait of the Japanese people and the pressing issues facing them today...During his decades of passionate engagement with Japan, Pulvers became close friends with many of the most gifted writers, filmmakers, actors and journalists in the country. Whether delving into ancient traditions or providing vivid accounts of contemporary customs, analyzing characters in Japanese fiction or recounting personal encounters with individuals, the author illuminates those inventive elements that have made Japanese culture and design the envy of the world--and that signal a way forward into the twenty-first century." -- Publisher's description.